Analysis of the Influence of Brand Image on Customer Loyalty Using Customer Satisfaction as an Intervening Variable Case Study at the Uni Kapau Jaya Restaurant, Bandung City - Permadhi, Billy Maulana; Maulina, Erna; Tresna, Pratami Wulan (International Journal of Science and Society, 2024)
This study aims to analyze the influence of brand image on customer loyalty with customer satisfaction as an intervening variable at Uni Kapau Jaya Restaurant, Bandung. The research method used is causal research with a quantitative approach. The research object is Uni Kapau Restaurant Jaya known for its Minang cuisine. Data were collected through surveys and statistically analyzed using the Structural Equation Modeling (SEM) technique. The results show a positive influence of brand image on customer loyalty, and customer satisfaction mediates the relationship between brand image and customer loyalty. The practical implications of this study emphasize the importance of considering brand image and customer satisfaction in enhancing customer loyalty in the food and beverage industry.